Determinants of the proportion of investment financing in Islamic banking business units in Indonesia - Muhamad Azumar Romzi; Deni Lubis (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Islamic banking in Indonesia has experienced rapid development, with Islamic Banking Business Units (UUS) offering an alternative Sharia-based financial system known as financing. However, the distribution of financing by Islamic banks remains predominantly consumptive rather than productive, with a direct connection to the real sector, such as investment financing, whose proportion or ratio to total financing disbursed diminishes annually. This study seeks to analyze the impact of internal and external factors on the proportion of investment financing in the UUS, including the Financing to Deposit Ratio (FDR), Investment Financing Margin, Non-Performing Financing (NPF), inflation, Gross Domestic Product (GDP), and the Certificate bonus Bank Indonesia Syariah (SBIS). The data period for this study spans from January 2018 to December 2023. The methodology employed in this study is the Vector Error Correction Model (VECM). The VECM analysis indicates that, in the short term, only the SBIS bonus variable significantly affects the proportion of investment financing. In the long term, GDP, inflation, and SBIS significantly influence the proportion of investment financing. UUS must develop strategies that are adaptive to external variables such as inflation, GDP, and SBIS. Additionally, UUS should promote accelerated growth in FDR and Margin.